The protective role of omentin-1 in IL-1β-induced chondrocyte senescence - Bin Chai; Zi-Hui Zheng; Xiang Liao; Kang-Yang Li; Jiang-Shan Liang; Yong-Xiang Huang; Chang-Jun Tong; Di-Jun Ou; Jun Lu (Artificial Cells, Nanomedicine, and Biotechnology)
Osteoarthritis is a common type of degenerative joint disease. Inflammation-related chondrocyte senescence plays a major role in the pathogenesis of osteoarthritis. Omentin-1 is a newly identified anti-inflammatory adipokine involved in lipid metabolism. In this study, we examined the biological function of omentin-1 in cultured chondrocytes. The presence of omentin-1 potently suppresses IL-1β-induced cellular senescence as revealed by staining with senescence-associated beta-galactosidase (SA-β-Gal). At the cellular level, omentin-1 attenuates IL-1β-induced G1 phase cell-cycle arrest. Mechanistically, we demonstrate that omentin-1 reduced IL-1β-induced expression of senescent factors including caveolin-1, p21, and PAI-1 as well as p53 acetylation through ameliorating SIRT1 reduction. Notably, silencing of SIRT1 abolishes IL-1β-induced senescence along with the induction of p21 and PAI-1, suggesting that the action of omentin-1 in chondrocytes is dependent on SIRT1. Collectively, our results revealed the molecular mechanism through which the adipokine omentin-1 exerts a beneficial effect, thereby protecting chondrocytes from senescence. Thus, omentin-1 could have clinical implication in the treatment of osteoarthritis.